The Syntactic-Semantic Analyses of Sasak Demonstratives in Lombok - Sutarman Sutarman; Nurachman Hanafi (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
Sasak language is spoken by approximately 3,352,888 people in Lombok, Indonesia. Typologically, it is a complex language because of its dual word orders. With its six dialectal varieties Meriaq-Meriqu, Menu-Meni, Ngeno-Ngene, Nggeto-Nggete, Meno-Meno and Kuto-Kute, Sasak language shows its unique properties in the use of demonstratives. This study dealt with Sasak demonstratives in Lombok with the aims to (a) syntactically and semantically examine their phenomena of demonstrative systems on six dialectal varieties, and (b) promote a typologically conceptual framework for assessing demonstratives. Data were gathered through interpretative elicitation, semi-interview to clarify the data, interpretative text by translating a document. Two fundamental concepts of Halliday & Hasan (1976), Diessel (1999), and Dixon (1988) on English demonstratives were used to analyze Sasak syntactic categories and semantic distinctions. The results showed that Sasak demonstratives are almost identical with English demonstratives in terms of their syntactic categories, but they are completely different in their semantic distinctions. Therefore, a new theoretical framework on the usage of demonstrative analyses across languages is recommended.